PUBLIC SERVICE MANAGEMENT IN MEURAXA HOSPITAL, BANDA ACEH CITY - Eko Prasetyo Budi; Arif Darmawan; Joko Widodo (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
Public service management is the process of planning, implementing, coordinating, and completing service activities to realize service goals. This study aimed to identify and analyze public service management and build an ideal service model at the Internal Medicine Polyclinic at Meuraxa Hospital, Banda Aceh City. This study used descriptive research method with a qualitative approach. Informants in this study consisted of outpatients, doctors, nurses, head of medical services, chair of the quality committee. The results of this study explained that the management of health services for outpatients of the Internal Medicine Polyclinic can be analyzed using professional service indicators, as follows: effective service, clarity and certainty (transparency), effective, timely service, responsiveness, and adaptability. This study concludes that outpatients feel satisfied with the services provided by the Internal Medicine Polyclinic.